Genealogi Transmisi Keilmuan Pesantren: Melacak Akar Pedagogi Kitab Ta'lim Muta'allim dari Era Nubuwah Hingga Tradisi Pesantren di Nusantara - Ahmad Wafa Izzulhaq Al Aziz (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2026)
This research aims to trace the genealogy of the pedagogical transmission of the book Ta’lim al-Muta’allim and to dissect the sociological reasons behind its fundamental position in the pesantren education system in Indonesia. Using a qualitative-descriptive method with a library research approach, this study is analyzed through Peter L. Berger’s sociology of knowledge framework to examine the processes of externalization, objectivation, and internalization of values within the pesantren. The results indicate that Ta’lim al-Muta’allim is a crystallization of the prophetic pedagogical tradition transmitted through the Nusantara ulama network (Haramain) in the 19th century. The prioritization of adab as a prerequisite before studying "instrument sciences" (Arabic linguistics) is not merely a curricular sequence, but a social construction ensuring that knowledge remains within the corridors of sacredness and blessing (barakah This book functions as a basis of epistemological legitimation that reinforces the collective identity of santri and preserves the tradition of Islamic education amidst the currents of pragmatic modernity. This study concludes that the strength of Ta’lim al-Muta’allim lies in its ability to transform classical ethics into a robust habitus, which maintains a balance between intellectual intelligence and moral integrity.